Sugar nation : the hidden truth behind America's deadliest habit and the simple way to beat it - O'Connell, Jeff, 1963- (New York : Hyperion, 2010)
The true story of one man's struggle to regain control of his life and save himself from his father's fate-- type 2 diabetes.
Ground zero: diabetes in the Delta -- Between the devil and the DNA -- White coats, white flags -- Metabolic mysteries -- Come, sweet death -- Grave consequence of denial -- Reading between the lines -- Prescriptions for a disaster -- Putting the'die' in diet -- Sweet surrender -- Losing the race to the cure -- Sinking feeling -- Barely a shadow cast -- Dissolved.
Includes bibliographical references (p. 273-292) and index.
Keywords: O'Connell, Jeff, -- 1963- -- Health; Non-insulin-dependent diabetes -- Popular works; Diabetes -- United States; Prediabetic state -- Patients -- United States -- Biography